Exploring structure-function coupling in alzheimer’s disease: bridging neuroimaging, AI, and policy for future insights - Wang, Xun; Jiang, Yixin; Dong, Yifan; Zhu, Qian; Zhao, Yan; Zhang, Shuo (European journal of nuclear medicine and molecular imaging, 2025)
[...]while the study focuses on static SFC metrics, it does not address dynamic network adaptations—such as time-varying functional connectivity or compensatory reorganization—that may influence cognitive resilience. Auto ML technology Just Add Data Bio generated three AD biosignatures using SVM (miRNA, AUC 0.975), Random Forests (mRNA, AUC 0.846), and Ridge Logistic Regression (protein, AUC 0.921) on low-sample blood omics data) [5]. [...]federated learning frameworks could harmonize data from multi-center, addressing current limitations in sample size and diversity [6]. GFAP as a potential biomarker for Alzheimer’s disease: A systematic review and Meta-Analysis.